THE EFFECT OF FINAL AND NON-FINAL TAX IN OPTIMAL CAPITAL STRUCTURE FOR FOUR STATE-OWNED COMPANIES IN THE CONSTRUCTION INDUSTRY (ADHI, WIKA, PTPP, AND WSKT) DURING PANDEMIC SITUATION - Made Nabil Akmal, Ngakan
Determining the company's capital structure is crucial because it is one of the parameters used to calculate the rate of return on investments. Furthermore, a business needs to determine the optimal capital structure related to increasing its value to benefit its shareholders. The COVID-19 pandemic has affected every industry in Indonesia, including the construction industry. Due to the pandemic, this industry experienced negative growth of -3.26% in 2020, concerning the performance of four construction SOEs, namely ADHI, WIKA, PTPP, and WSKT. Furthermore, the debt to equity ratios of the four companies increases year after year, affecting each company's cost of capital. ADHI, WIKA, PTPP, and WSKT have diversified their businesses so that they are no longer focused primarily on construction services but have non-construction businesses such as energy, industrial plants, equipment, toll-road revenues, and so on. As a result, these businesses are subject to two types of taxes: final and non-final taxes. As a result, the optimal capital structure of the four companies is also affected. Before the COVID-19 pandemic, the optimal capital structure of ADHI, WIKA, PTPP, and WSKT was 0% debt and 100% equity because the majority of the company's income was from construction services subject to final tax. However, as non-taxable income decreases and taxable income increases, the four companies' optimal capital structures differ in pandemic situations.